LITERATURE REVIEW: ANALYSIS OF DIGITAL BUSINESS MODEL INNOVATION (IMPLICATIONS FOR OFFERINGS, PATFORMS AND ORGANIZATIONS) - Nalom Siagian (Universitas Efarina, 2020)
This literature will discuss how to explore the main challenges for manufacturing companies that seek to innovate business models in the era of digitalization. The research method used in this paper is qualitative research based on a literature review study. The method used is empirical observation originating from information sources. First, there is an internal company survey. Second, semi-structured interviews were conducted with managers and directors of sales and product management. Based on the results of observations of the Husqvarna company case study, it is revealed that the movement towards a new business model is important to understand which services are truly in demand by the customer base. In this case, platform strategy is important because it is the key to supporting increased variety and moreover reducing costs and time in the marketing process. So companies must be able to build platforms quickly, efficiently and flexibly, especially if they have to develop a variety of products and services. This case study comes to the conclusion that organizations need to become more complex and there are many parts of the company that will change the way they work at the same time. Therefore, there is a high drive towards achieving the integration of knowledge and useful activities. So the sale of products and services is very different from the time of company management and requires the flow of new value within the company.